PRE-PREGNANCY TRAINING OF WOMEN WITH CORRECTION OF CARBOHYDRATE METABOLISM BEFORE REPEATED CYCLES OF ART WITH SEVERE ENDOMETRIAL INSUFFICIENCY (World Science, 2021)
According to statistics, every fifth married couple has problems with pregnancy. It is known that among all the factors of infertility, the first place is occupied by the tubal-peritoneal factor, and the most common cause of non-pregnancy is a violation of the receptive ability of the endometrium. In the study of the endometrium in patients with unsuccessful attempts at assisted reproductive technologies and severe endometrial insufficiency, there are changes in receptivity, impaired development of foaming, decreased expression of implantation molecules. The development of new methods for correcting the receptive function of the endometrium remains an important step. It should be noted that currently there are no standardized approaches to pre-pregnancy preparation of endometrial receptivity with pronounced signs of lag. Also today, special attention is paid to the impact of carbohydrate metabolism disorders on women's reproductive health. Based on the analysis of literature data and the results of their own retrospective observations, the team of authors identified the role of disorders of carbohydrate metabolism and autoimmunization with food allergens in the violation of endometrial receptivity. It is noted that severe endometrial insufficiency is significantly correlated with an increase in the number of women with disorders of carbohydrate metabolism. The initial algorithm of preliminary preparation of the endometrium of normal immune systems and carbohydrate conversion of heirs in accordance with the mode of processing and analysis is developed and offered. Created, adherence to the elimination diet increases the receptivity of the endometrium with a collection of women according to standard schemes. The proposed training algorithm also improves the overall health of patients, reduces metabolic manifestations.The results of the studies indicate the need for a differentiated approach to the correction of endometrial receptivity and pre-pregnancy preparation of the endometrium before subsequent cycles of ART.